2021
DOI: 10.36315/2021inpact049
|View full text |Cite
|
Sign up to set email alerts
|

Ideas About Marriage Depending on the Structure of Valuable Orientations of Women in Early Adulthood

Abstract: "The phenomenon of marriage is one of the little-studied questions of family psychology. The resolution of the contradiction between the need of modern society to form complete and adequate ideas about the marital role among students and the need to identify socio-psychological factors that influence the development of ideas about marriage determines the problem of research. The purpose of the study is to identify the features of ideas about marriage (Ideal husband, Ideal wife) depending on the structure of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…So, the obtained results show that the structure of valuable orientations is associated with the content characteristics of ideas about marriage among young women in early adulthood. The results of the study are consistent with our data obtained in an earlier study on a sample of young students, which shows that the structure of valuable orientations determines the peculiarities of ideas about marriage among young men in adolescence and early adulthood (Merzlyakova, Golubeva, & Bibarsova, 2020). However, a comparative analysis shows that the ideas of an ideal husband and an ideal wife do not coincide among young men and young women with the same structure of valuable orientations.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…So, the obtained results show that the structure of valuable orientations is associated with the content characteristics of ideas about marriage among young women in early adulthood. The results of the study are consistent with our data obtained in an earlier study on a sample of young students, which shows that the structure of valuable orientations determines the peculiarities of ideas about marriage among young men in adolescence and early adulthood (Merzlyakova, Golubeva, & Bibarsova, 2020). However, a comparative analysis shows that the ideas of an ideal husband and an ideal wife do not coincide among young men and young women with the same structure of valuable orientations.…”
Section: Discussionsupporting
confidence: 90%
“…The image of their own father is a guide in the formation of ideas about ideal husband only for young women who are focused on the values of personal life. A comparative analysis with our data obtained in an earlier study on a sample of young students (Merzlyakova, Golubeva, & Bibarsova, 2020) indicates that the content characteristics of the "Ideal Husband" image do not coincide among young men and women who are focused on the values of professional self-realization and the values of personal life. Other authors obtained the similar results in their studies: they recorded gender differences in the ideas of parenthood among high school students (Zakharova et al, 2019).…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…For adolescent young women with a focus on the values of professional self-realization, the image of "Ideal husband" reveals elements of cognitive, emotional and behavioral components. Earlier research in this area has shown that the idea of an ideal husband in early adulthood is limited to the content characteristics of the cognitive and emotional components (Merzlyakova & Golubeva, 2021). If in adolescence the ideas of an ideal wife among young women have elements of cognitive and behavioral components, then in early adulthood, only the cognitive component is formed.…”
Section: Discussionmentioning
confidence: 99%
“…The image of the ideal wife among young women focused on gnostic and aesthetic values is characterized by the presence of cognitive distortions which are manifested in a negative attitude towards the family as a social institution, the low importance of parental and educational functions and the role of the mother (Merzlyakova & Golubeva, 2021). At the same time the importance of such a parameter of morality as a moral orientation of the personality for the development of ideas about an ideal marriage partner has not been investigated.…”
Section: Introductionmentioning
confidence: 99%